QCD equation of state and thermodynamic observables from computationally minimal Dyson-Schwinger equations - Lu, Yi; Gao, Fei; Liu, Yu-xin; Pawlowski, Jan M. (Physical review, 2024)
We study the QCD equation of state and other thermodynamic observables including the isentropic trajectories and the speed of sound. These observables are of eminent importance for the understanding of experimental results in heavy ion collisions and also provide a QCD input for studies of the timeline of heavy-ion-collisions with hydrodynamical simulations. They can be derived from the quark propagator whose gap equation is solved within a minimal approximation to the Dyson-Schwinger equations (DSEs) of QCD at finite temperature and density. This minimal approximation aims at a combination of computational efficiency and simplification of the truncation scheme while maintaining quantitative precision. This minimal DSE scheme is confronted and benchmarked with results for correlation functions and observables from lattice QCD at vanishing density and quantitative functional approaches at finite density.